Development of Reflexive Processes from the Perception of Nursing Students - Olate, Jessica; Castillo, Silvana (Revista de Psicología, 2017)
This research was performed at the end of a subject taught in the second year of Nursing, whose purpose was to contribute to the integral formation of the student, through self-knowledge and development of social skills to favor the establishment of therapeutic relationships. Strategies were used to intend the development of the reflection, and it was pertinent to investigate the perception of the students on their own reflective processes. The aim was to explore how nursing students perceive the development of their reflective processes. It was a naturalistic research, which used a qualitative method to study a single and intrinsic case; semi-structured interviews were carried out, after signing an informed consent by students. An inductive data analysis was performed using the constant comparison method. As results three related thematic groups emerged: development of the reflective process, team work experiences and development of meaningful learning. It was concluded that reflective processes of nursing students correspond to a recursive phenomenon that become deep and mature over time. This process is perceived as the development of a skill, which is identified as useful not only in a personal level, but also as an academic tool and as future professionals.